Pengaruh Penggunaan Media Kartu Warna Terhadap Keterampilan Membaca Pantun Siswa Kelas V UPTD SDN Negeri 98 Barru - Sahir Sahir; Sulfasyah Sulfasyah; Tarman A. Arif (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is to describe the effect of using color card media on rhyme reading skills in class V UPTD SDN Negeri 98 Barru students. This type of research uses pre-experimental designs with a one-group pretest-posttest design type, namely an experiment whose implementation only involves one class without involving other classes (comparison class) which aims to find out the use of color card media in reading rhymes among class V UPTD students at SDN Negeri 98 Barru. The sample in this research was class V UPTD students at SDN Negeri 98 Barru with a total of 21 students. The data collection techniques used were observation, tests and documentation. The data was analyzed using descriptive statistics. The results of the research concluded that the use of color card media had an effect on rhyme reading skills. This shows that before using the color card media it was classified as low with a score of 45 and the highest score was 85. However, after using the color card media the pantun reading skill was relatively high with the lowest score being 65 and the highest score being 100. So if it is linked to the category of learning outcomes after reading the pantun or given color card media in the very good category, there were 65%, 25% good, 10% fair and 0% less. Based on the hypothesis test that has been carried out, it can be concluded that the use of color card media has an influence on the rhyme reading skills of class V UPTD SDN Negeri 98 Barru. After obtaining tcount= 9.811 and ttable= (0.05= 1.725, we obtained 9.811 > 1.725. So these results show that after being given color card media it has a positive effect because the tcount value is greater than the ttable value.